The Use of Learning Management System (LMS): Are we ‘using’ it right? (Journal of Applied Learning and Teaching, 2021)
Due to the rapid progress of the use of technologies in academic practices, higher education institutions around the world are investing heavily in various learning management systems (LMS). LMS, such as Blackboard, is considered among the most commonly used in the process of teaching and learning. This pilot study aimed to identify the academics’ assumptions and expectations of Blackboard use that had influences on their practices at a New Zealand university. Data were gathered through class observation sessions with photograph and video capture as well as individual discussions for a trimester (13 weeks). Focus of the thematic analysis was on the viewpoints expressed by the academic participants on their Blackboard courses and in their discussions, as well as in their classes about their ideas, practices, and beliefs in relation to their Blackboard use. The major findings that emerged from the data were the diverse perspectives of the roles of Blackboard in the process of teaching and learning that led to the questionable use of Blackboard in terms of “efficiency” and “effectiveness”. It is evident that explicit support needs to be provided to academics in order for them to understand the affordances of Blackboard and thus to use Blackboard pedagogically in the process of teaching and learning. The study advocates for a shift of Blackboard use in relation to a new understanding of teaching and learning schemas in higher education.